1997
DOI: 10.1007/bf03039191
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapie im frühen Stadium des Morbus Dupuytren

Abstract: Radiotherapy prevents disease progression for early stage Dupuytren's contracture. Thus, an otherwise necessary surgical procedure in advanced stages of Dupuytren's contracture can be avoided. Moreover, in case of disease progression despite radiotherapy a second radiotherapy or salvage operation is still feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…Radiotherapy has been reported to be effective for prevention of disease progression in early stages with only mild acute or late side effects (RTOG grade 1/2) [1,11,12]. The progression of Dupuytren's contracture may be slowly, some cases show stabilization or even spontaneous regression; therefore, a possible therapeutic effect of any treatment should be assessed in long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy has been reported to be effective for prevention of disease progression in early stages with only mild acute or late side effects (RTOG grade 1/2) [1,11,12]. The progression of Dupuytren's contracture may be slowly, some cases show stabilization or even spontaneous regression; therefore, a possible therapeutic effect of any treatment should be assessed in long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…More recent publications using a total dose of 21 Gy found improvement or stabilization of symptoms in 91% of the patients vs. 93% in a group of patients irradiated with a total dose of 30 Gy after a follow‐up time of 12 months. Using total doses from 30 to 32 Gy for improvement or stabilization of DD was also confirmed in other studies in 98% (follow‐up >18 months) #bib95% (follow‐up >3 years), 80% (median follow‐up of 4 years and 4 months), 100% (follow‐up up to 5 years) and 94% (follow‐up with a median of 6 years)of the patients. A study using a cumulative dose of 40 Gy showed an improvement or stabilization in 93% (follow‐up up to 9 years) and another with 20 Gy in 82% (follow‐up up to 2.5 years)of the patients.…”
Section: Radiation Therapymentioning
confidence: 53%
“…Follow‐up for a decade or longer (median: 13 years) showed a progression of DD in 22% or 31% of the patients respectively; follow‐up between 4 and 10 years showed a progression in 12% #bib23% or 20%, and effects depended on the disease stage when patients were treated (see above). In one study #bib19% of the patients developed new DD lesions in non‐irradiated areas after a median of 10 years.…”
Section: Radiation Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…Die perkutane Strahlentherapie des Morbus Dupuytren wurde bereits in der Literatur von verschiedenen Autoren beschrieben [12,13,17,21,24,35,41]. Von den ca.…”
unclassified